2015
DOI: 10.4103/0973-6247.154258
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and serological characterization of cold agglutinin syndrome in a Tertiary Care Hospital in Eastern India

Abstract: Background and Aim:Cold agglutinin syndrome (CAS) primary or secondary represents approximately 16-32% of autoimmune hemolytic anemia cases. Most patients present with mild, chronic hemolytic anemia with exacerbation of the condition in the cold environment. Red cell transfusions are only indicated when there is a life-threatening anemia causing crisis. We studied the clinical and serological characterization of CAS with the aim that the information gained from this study would help in proper diagnosis and man… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 13 publications
0
7
0
Order By: Relevance
“…Otherwise, most articles describe large variation in the CA titer between individual patients with CAD/CAS, but an evaluation of a correlation between the titer and the hemolytic degree in vivo is missing 43,50–52 . Pla et al showed a titer range of 32–2048 in patients with CAD/CAS, in comparison with a titer of 16 in healthy donors, without a reported correlation titers and the degree of hemolysis 53…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Otherwise, most articles describe large variation in the CA titer between individual patients with CAD/CAS, but an evaluation of a correlation between the titer and the hemolytic degree in vivo is missing 43,50–52 . Pla et al showed a titer range of 32–2048 in patients with CAD/CAS, in comparison with a titer of 16 in healthy donors, without a reported correlation titers and the degree of hemolysis 53…”
Section: Discussionmentioning
confidence: 99%
“…To what extent the antibody specificity indicates severity of the disease, remains unknown. In only 6/13 case series performing testing on CA specificity, the CA specificity was described as either being correlative or used to confirm the diagnosis in patients with CAD/CAS 43,45,48,51,56,57 . In the case series by Sokol et al, with 121 patients, the most common autoantibody specificity was anti‐I 57 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[ 2 ] Under some circumstances, the exacerbations of CAS could lead to acute hemolysis, jaundice, and even acute renal dysfunction when the patients are in a cold environment. [ 3 ] Most cases of CAS are complicated with lymphoma, and some other hematological malignancies and cases of CAS with solid tumors have been seldom reported. [ 4 ] Surgical resection is always the unique way to achieve curative outcome for the solid tumor patients.…”
Section: Introductionmentioning
confidence: 99%